Dose evaluation for common digital radiographic examinations in selected hospitals in Pahang Malaysia - Moey, Soo Foon; Ahmad Shazli, Zubir; Shah, Sayed Inayatullah (Iranian Association of Medical Physicists, 2017)
Introduction: In digital radiography, radiographers tend to increase exposure factors to acquire an acceptable image quality thereby increasing radiation dose to patients. Regarding this, the present study aimed to re-evaluate the exposure parameters and to ascertain the entrance surface dose (ESD) and effective dose (ED) of posterior-anterior (PA) chest, abdomen, and anterior-posterior (AP) lumbosacral spine radiography. Materials and Methods: This study was conducted on 180 physically able patients with age of 20-60 years and weight of 60-80 kg referred to Hospital Sultan Haji Ahmad Shah (HOSHAS) and Hospital Tengku Ampuan Afzan (HTAA).Image acquisition was performed using digital radiography. The ESD and ED were determined using CALDose_X 5.0 software. Results: The ESD and ED for PA chest were 0.098 mGy and 0.012 mSv in HOSHAS, while in HTAA were 0.161 mGy and 0.021 mSv respectively. Regarding the abdomen, the ESD and ED were 2.57 mGy and 0.311 mSv in HOSHAS and 2.16 mGy and 0.262 mSv in HTAA respectively. For AP lumbosacral spine, the ESD and ED for HOSHAS were 2.65 mGy and 0.222 mSv, while in HTAA were 2.357 mGy and 0.201 mSv respectively. Conclusion: The findings revealed the use of high kVp, automatic exposure control, correct focus image receptor distance, tight collimation and additional filter resulted in a lower ESD. The ESD and ED obtained in this study were comparable with those reported by other studies and lower than the values recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation in 2008